A Bithiophene‐based Ratiometric Fluorescent Sensor for Sensing Cd2+. Issue 32 (26th August 2021) - Lee, Su Chan; Lee, Minji; Suh, Boeon; Lee, Jiyoung; Kim, Cheal
Abstract: A novel bithiophene‐naphthalene based ratiometric fluorescent chemosensor SS ((2E, 2′E)‐2, 2′‐([2, 2′‐bithiophene]‐5, 5′‐diylbis(methanylylidene)) bis(N‐(naphthalen‐1‐yl) hydrazine‐1‐carbothioamide)) for detecting Cd 2+ was prepared. SS can detect Cd 2+ by a ratiometric fluorescent response with red‐shifted emission from 500 to 540 nm. The binding ratio of SS and Cd 2+ was determined to be a 1 : 1 stoichiometry via Job plot. The detection limit was found to be 4.41 μM. The association constant (K) was calculated as 3.00×10 2  M −1 . Sensor SS was successfully applied in real water samples and fluorescent test kits for analysis of Cd 2+ . The sensing process of SS towards Cd 2+ was illustrated by fluorescent, UV‐vis and NMR spectroscopy, ESI‐MS (electrospray ionization‐mass spectrometry), FT‐IR (Fourier transform‐Infrared spectroscopy) and calculations. Abstract : A novel bithiophene‐naphthalene based ratiometric fluorescent probe SS ((2E, 2′E)‐2, 2′‐([2, 2′‐bithiophene]‐5, 5′‐diylbis(methanylylidene)) bis(N‐(naphthalen‐1‐yl) hydrazine‐1‐carbothioamide)) is developed for detecting Cd 2+ . Sensor SS can successfully distinguish Cd 2+ from Zn 2+ and quantify Cd 2+ in real samples. The detection limit of SS for Cd 2+ is determined to be 4.41 μM. The Cd 2+ ‐triggered binding property of SS is studied by variant spectroscopic methods and density functional theory calculations.